PENGARUH REMUNERASI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA ANGGOTA POLISI SATUAN LALU LINTAS POLRES KENDARI - Debby Aulia; Aidin Hudani Awasinombu; Yusuf Montundu; Hastuti Hastuti (Pascasarjana Universitas Halu Oleo, 2022)
This study aims: 1) to find out the effect of remuneration, organizational culture and job satisfaction on the performance of members of the Kendari Police Traffic Unit, 2) to determine the effect of remuneration partially affecting the performance of Kendari Police Traffic Unit police officers, 3) to find out organizational culture has a significant effect on the performance of the Kendari Police Traffic Unit. partial effect on the performance of the members of the Traffic Unit of the Kendari Police, 4) knowing that job satisfaction has a partial effect on the performance of the members of the Traffic Unit of the Kendari Police.The object of this research is the Kendari Police Traffic Unit. The population of the study was police officers who served in the Traffic Unit of the Kendari Police with a total of 63 personnel. Determination of the sample using population data. The research data was collected using a questionnaire, the research data was analyzed using SPSS ver 22 to determine the results of the regression analysis of the influence of the independent variable on the dependent variable.The results of the study: 1) Remuneration, organizational culture, and job satisfaction simultaneously have a positive and significant effect on the performance of members of the Kendari Police Traffic Unit, 2) Remuneration has a positive and significant effect on the performance of Kendari Police Traffic Unit members, )3 Organizational culture positive and significant effect on the performance of the Traffic Unit Police members of the Kendari Police, and 4) Job satisfaction has a positive and significant effect on the performance of the members of the Kendari Police Traffic Unit